First‐in‐human clinical trial to assess the safety, tolerability and pharmacokinetics of P218, a novel candidate for malaria chemoprotection. Issue 6 (12th February 2020) - Chughlay, M. Farouk; Rossignol, Emilie; Donini, Cristina; El Gaaloul, Myriam; Lorch, Ulrike; Coates, Simon; Langdon, Grant; Hammond, Tim; Möhrle, Jörg; Chalon, Stephan
Abstract : Aims: This first‐in‐human clinical trial of P218, a novel dihydrofolate reductase inhibitor antimalarial candidate, assessed safety, tolerability, pharmacokinetics and food effects in healthy subjects. Methods: The study consisted of two parts. Part A was a double‐blind, randomized, placebo‐controlled, parallel group, ascending dose study comprising seven fasted cohorts. Eight subjects/cohort were randomized (3:1) to receive either a single oral dose of P218 (10, 30, 100, 250, 500, 750 and 1000 mg) or placebo. Part B was an open‐label, cross‐over, fed/fasted cohort (eight subjects) that received a 250 mg single dose of P218 in two treatment periods. Results: P218 was generally well tolerated across all doses; 21 treatment‐emergent adverse events occurred in 15/64 subjects. Nine adverse events in five subjects, all of mild intensity, were judged drug related. No clinically relevant abnormalities in ECG, vital signs or laboratory tests changes were observed. P218 was rapidly absorbed, with C max achieved between 0.5 and 2 hours post dose. Plasma concentrations declined bi‐exponentially with half‐life values ranging from 3.1 to 6.7 hours (10 and 30 mg), increasing up to 8.9 to 19.6 hours (doses up to 1000 mg). Exposure values increased dose‐proportionally between 100 and 1000 mg for P218 (parent) and three primary metabolites (P218 β‐acyl glucuronide, P218‐OH and P218‐OH β‐acyl glucuronide). Co‐administration of P218 with food reduced C max by 35% and delayed absorption by 1 hour, with no significant impact on AUC. Conclusion: P218 displayed favourable safety, tolerability and pharmacokinetics. In view of its short half‐life, a long‐acting formulation will be needed for malaria chemoprotection.